2011
DOI: 10.1080/19439342.2011.570450
|View full text |Cite
|
Sign up to set email alerts
|

Does social capital build women's assets? The long-term impacts of group-based and individual dissemination of agricultural technology in Bangladesh

Abstract: This paper investigates the long-term impact of agricultural technologies, disseminated using different implementation modalities on men's and women's asset accumulation in rural Bangladesh. Panel data spanning a 10-year period are used to examine the effects of the adoption of new vegetable varieties and polyculture fish pond management technologies on household resource allocation, incomes, and nutrition. A difference-in-differences model combined with nearest-neighbour matching is used to compare changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…In a CARE evaluation in Bangladesh, Patt, Dazé, and Suarez (2009) find the adaptation strategies taken most by women were those that could be adopted in the homestead, such as duck rearing. Hallman, Lewis, and Begum (2007) and Quisumbing and Kumar (2011) evaluate the uptake of group vegetable and fishpond interventions in Bangladesh and find women have more success with vegetable gardens that could take place at the homestead and did not require excessive mobility. All of this being said, roles and norms will change depending on country and context, and CBA strategies will need to be appropriately adjusted.…”
Section: Gendered Priorities For Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a CARE evaluation in Bangladesh, Patt, Dazé, and Suarez (2009) find the adaptation strategies taken most by women were those that could be adopted in the homestead, such as duck rearing. Hallman, Lewis, and Begum (2007) and Quisumbing and Kumar (2011) evaluate the uptake of group vegetable and fishpond interventions in Bangladesh and find women have more success with vegetable gardens that could take place at the homestead and did not require excessive mobility. All of this being said, roles and norms will change depending on country and context, and CBA strategies will need to be appropriately adjusted.…”
Section: Gendered Priorities For Adaptationmentioning
confidence: 99%
“…More generally, institutions affect the roles governing access to and control over resources and assets for adaptation (Jones, Ludi, and Levine 2010). Social and cultural norms, and other rules governing behavior, influence the extent to which individuals and groups within a community are able to participate in and benefit from collective action (Thomas et al 2007;Eriksen and Lind 2009;Patt, Dazé, and Suarez 2009;Quisumbing and Kumar 2011).…”
Section: Framework For Adaptation To Climate Changementioning
confidence: 99%
“…In an examination of the same project we focus on here, Kumar and Quisumbing (2010;Quisumbing and Kumar 2011) found that the program's group-based dissemination technique caused women's ownership of assets to increase at a faster rate than men's. The social capital fostered by women's groups helped participants increase their bargaining power and accumulate more assets.…”
Section: Women's Group-based Fish Polyculture Program In Bangladeshmentioning
confidence: 99%
“…As Kumar and Quisumbing (2010;Quisumbing and Kumar 2011) noted, the dissemination of gender-sensitive agricultural technologies is complex and contingent on existing economic arrangements and cultural contexts. As a result, women-based modalities may be successful in some venues (see, e.g., Ashaletha et al 2002;Kripa and Surendranathan 2008) while having severe limitations and/or unexpected consequences in others.…”
Section: Women's Group-based Fish Polyculture Program In Bangladeshmentioning
confidence: 99%
“…We present results from the quantitative longitudinal impact evaluation on the program's impact on men's and women's assets, and then provide a more nuanced interpretation of that impact using two rounds of qualitative research. 4 Whereas some studies on the impacts of agricultural interventions on various measures of women's empowerment have demonstrated increases in women's income, control over income, or participation in household decision making (for example, Bushamuka et al 2005;HKI 2004HKI , 2006Iannotti, Cunningham, and Ruel 2009;Mullins et al 1996;Nielsen 1996), others have found no such impacts (for example, Begum 1994;Hagenimana et al 1999;Mulokozi et al 2000) or mixed results (Brugere, McAndrew, and Bulcock 2001;Kumar and Quisumbing 2011;Naved 2000;Quisumbing and Kumar 2011). In some cases men saw a higher increase in income than did women (Begum 1994;Tangka, Ouma, and Staal 1999), seemed to maintain control over income and household resources (Hagenimana et al 1999;Tangka, Ouma, and Staal 1999), maintained control over higher-value assets, or took over control of certain assets as they became more profitable (Carney 1988;von Braun and Webb 1989).…”
Section: Introductionmentioning
confidence: 99%